2015
DOI: 10.1111/mmi.12970
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pseudotuberculosisYopDmutants that genetically separate effector protein translocation from host membrane disruption

Abstract: SummaryThe Yersinia type III secretion system (T3SS) translocates Yop effector proteins into host cells to manipulate immune defenses such as phagocytosis and reactive oxygen species (ROS) production. The T3SS translocator proteins YopB and YopD form pores in host membranes, facilitating Yop translocation. While the YopD amino and carboxy termini participate in pore formation, the role of the YopD central region between amino acids 150-227 remains unknown. We assessed the contribution of this region by generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Additional bacterial factors are important for fine-tuning effector translocation. The Yersinia cytotoxic necrotizing factor-γ produced by certain strains activates Rac-[27] and Rho-GTPases [28] to enhance Yop translocation into target immune cells, while structure-function studies reveal regions within the transolocon component YopD to be important for effector delivery [2931]. …”
Section: Later Interactions Of Yersinia With Host Cells-important Formentioning
confidence: 99%
“…Additional bacterial factors are important for fine-tuning effector translocation. The Yersinia cytotoxic necrotizing factor-γ produced by certain strains activates Rac-[27] and Rho-GTPases [28] to enhance Yop translocation into target immune cells, while structure-function studies reveal regions within the transolocon component YopD to be important for effector delivery [2931]. …”
Section: Later Interactions Of Yersinia With Host Cells-important Formentioning
confidence: 99%
“…Additional evidence demonstrates that the translocon pore, rather than simply a conduit for effector secretion, functions in an active capacity to regulate effector secretion [7, 10]. Discrete mutations in translocon pore proteins have been identified that do not alter the efficiency of translocon pore formation but restrict the efficiency of docking or effector translocation [7, 14], which shows that translocon pore formation per se is not sufficient for T3SS function.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge is limited concerning the stepwise biogenesis of the T3SS translocon pore and its relationship toward effector protein translocation. Encouragingly, recent mutagenesis studies of the YopD translocator have been able to genetically demarcate discrete functional domains [ 29 , 32 , 33 , 51 , 59–61 ]. This hints at the possibility that YopD mutants could be generated that have targeted deficits in one or a few phenotypes in isolation from all others.…”
Section: Discussionmentioning
confidence: 99%